Eksplorasi Potensi Kampung Wisata Rumah Tuo di Merangin Provinsi Jambi yang Menjanjikan - widya fitri; Siti Fatimah (Jurusan Sejarah FIS UNP, 2022)
As a tourist village, Kampung Rumah Tuo is a traditional village that is hundreds of years old and still survives today. Kampung Rumah Tuo has the potential to become an attraction for tourists to visit, namely the tangible culture and intangible culture found in Kampung Rumah Tuo, with the diversity of potentials that make this tourism object promising in Merangin Regency. The purpose of this study is to describe the potentials of Kampung Rumah Tuo as a tourist attraction. The method used is the historical method which consists of four stages, namely heuristics, criticism, interpretation and historiography. Based on the results of this study, the Tuo House Tourism Village is an old village that is hundreds of years old that still survives. With old buildings of high value with a total of 60 houses that still survive. Not only old houses but in Kampung Rumah Tuo there is also a tangible culture and intangible culture that is still original so that it becomes a potential as a tourism object that deserves to be promoted. Keywords: Tourism Village, Tuo's House, Potential, Tourist Attraction, Baruh Village, Merangin